지식 민주주의 시대의 사회적 혁신을 위한 기업가적 대학의 역할: 쿼드러플 힐릭스 모형을 중심으로 - 남수연; Souyeon Nam (한국경제지리학회지, 2024)
본고는 쿼드러플 힐릭스 모형에서 사회 분야에 초점을 두고 대학의 역할을 모색하여 정책적 시사점을 제공하는 것을 목적으로 한다. 쿼드러플 힐릭스 모형은 사회 변화 반영의 한계를 보이는 트리플 힐릭스 모형을 보완하여, 지식의 민주주의를 기반으로 다양한 사회 주체 간 상호작용을 통해 혁신을 창출하는 과정을 제시한다. 이를 기반으로 본고는 기업가적 대학 모형에 지식의 민주주의와 사회적 혁신 이론을 검토한 결과를 적용한 ‘사회 기업가적 대학’ 모형을 제안한다. 사회적 민주화 및 포용성이 담보된 쿼드러플 힐릭스 모형에서 사회 기업가적 대학은 교육의 역할을 강화하는 한편, 지역민을 포함한 광범위한 지역 주체의 상호작용을 구조화 및 촉진하는 플랫폼을 조성 및 촉진하는 데 교육 및 연구 역량을 할애하는 것이 중요하다. This paper aims to provide policy implications by exploring the role of universities in the Quadruple Helix model with a focus on the social sector. The quadruple helices model complements the triple helices model, which has limitations in reflecting social change, to present a process of innovation creation through interaction between various social actors based on the democracy of knowledge. Based on this, this paper proposes a ‘social entrepreneurial university’ model that applies the results of the review of democracy of knowledge and social innovation theory to the entrepreneurial university model. In the quadruple helix model of social democratization and inclusion, it is important for social entrepreneurial universities to enhance the role of education, while dedicating their teaching and research capacities to creating and facilitating platforms that structure and promote the interaction of a wide range of local actors.